Maternal alcohol consumption and altered miRNAs in the developing fetus: Context and future perspectives. Issue 1 (5th July 2017) - Mandal, Chanchal; Halder, Debasish; Jung, Kyoung Hwa; Chai, Young Gyu
Abstract: Alcohol is a teratogenic agent that can cause a wide range of developmental disorders, and sometimes, the effects persist throughout an individual's lifetime. Researchers have shown the involvement of epigenetic mechanisms in alcohol‐mediated disorders. Non‐coding RNAs are one of the major sources of epigenetic modifications, especially microRNAs. The association of microRNAs with alcohol consumption leads to a new focus on finding the molecular mechanisms of alcohol toxicity. It has been suggested that alcohol alters the relative expression of microRNAs and regulates target mRNA expression in both in vitro and in vivo models. Currently, we lack information regarding the relationship between altered microRNA expression and disease phenotypes in alcohol‐mediated disorders. In this review, we tried to gather all of the available information about the alcohol‐mediated dysregulation of microRNA expression in utero. We hope that our efforts will help future researchers identify major microRNAs in the field of prenatal alcohol toxicity and related therapeutics. Abstract : Researchers have shown the involvement of epigenetic mechanisms in alcohol‐mediated disorders. Non‐coding RNAs are one of the major sources of epigenetic modifications, especially microRNAs. The association of microRNAs with alcohol consumption leads to a new focus on finding the molecular mechanisms of alcohol toxicity.